Soil Moisture Estimation by GNSS-IR from Active Stations: Case Study – RBMC/IBGE, UFPR Station - Euriques, Jorge Felipe; Veiga, Luis Augusto Koenig; Machado, Wagner Carrupt; Krueger, Claudia Pereira; Geremia-Nievinski, Felipe (Anuário do Instituto de Geociências, 2025)
The Earth is a dynamic planet subject to numerous natural phenomena and processes that human activities have intensified. Monitoring variables associated with these phenomena is essential. Soil moisture, for example, plays a crucial role in climate systems, agriculture, and the hydrological cycle. The Global Navigation Satellite Systems (GNSS) is one of the Geodesy tools used for monitoring the Earth, through which the GNSS Interferometric Reflectometry (GNSS-IR) technique can be employed to estimate soil moisture. In this study, the UFPR station, part of the Brazilian Continuous Monitoring Network of GNSS Systems (RBMC) was selected for investigation. A Python script was developed to automate the preparation of GNSS data from any RBMC station. Different processing configurations of a reflectometric algorithm were evaluated, resulting in a set of time series of soil moisture for 2022. Results indicate that configurations adapted to the station’s local conditions contribute to the enhancement of the results. The best signal among the 24 evaluated was the precise signal from the L2 frequency of GLONASS (RS2P). Peaks in precipitation were aligned with peaks in soil moisture, with soil moisture ranging from 0 to 0.35 m³/m³. The results support the development of a methodology for monitoring soil moisture in the vicinity of GNSS-RBMC stations that meet GNSS-IR requirements, expanding the potential applications of this network.